Intraoperative Gallbladder Scoring Predicts Difficulty of Surgery and Conversion of Laparoscopic to Open Cholecystectomy - Umer, Waleed; Naqvi, Rifaat Qamar; Shakil, Fahad; Tariq, Mansoor (Pakistan Armed Forces Medical Journal, 2024)
Objective: To determine the ability of “Gallbladder Operating Score (G10)” to predict difficulty of surgery and timely conversion of laparoscopic to open cholecystectomy. Study Design: Cross sectional study. Place and Duration of Study: General Surgery Unit of Combined Military Hospital, Rawalpindi Pakistan, from Nov 2021 to Nov 2022. Methodology: One hundred and eleven cases scheduled to undergo laparoscopic cholecystectomy were recruited. After an informed consent age, gender, Body Mass Index, G10 score and category of severity ranging from mild to extreme was documented. Operative time was documented to define difficult cholecystectomy alongside conversion of laparoscopic to open cholecystectomy. Results: A total of 111[53(47.70%) male and 58(52.30% female)] cases who were scheduled to undergo laparoscopic cholecystectomy were included with mean age of 43.36±5.33 years. Median G10 score of patients was 3.00 (range: 1.00-8.00). Overall frequency of conversion from laparoscopic to open cholecystectomy was 9(8.10%). G10 between the study participants who experienced conversion of laparoscopic to open cholecystectomy as compared to those who had their laparoscopic cholecystectomy completed was statistically significant (p=0.003). Conclusion: Gallbladder Operating Score (G10) is helpful in predicting the difficulty cholecystectomy and conversion of laparoscopic to open cholecystectomy.